2008
DOI: 10.1108/09685220810908769
|View full text |Cite
|
Sign up to set email alerts
|

Escalation and premature termination in MIS projects: the role of real options

Abstract: PurposeThe purpose of this paper is to examine how the real option theory is applicable to evaluation of cases of escalation and premature termination of Management Information Systems (MIS) projects.Design/methodology/approachThe paper compares the implications of psychological and economic escalation theories with lessons from the real option theory as applied to MIS projects. Then, it examines published case studies, and discuss when project continuation enhances and reduces value for the manager and the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…As mentioned above, current studies that measured the value of risky projects and used NPV or ROA stopped at the initial decision and neglected to investigate the impact of the way the project is managed on its business value. A project includes one or more real option opportunities when managers have the option, but not the obligation to adjust the future direction of the project in response to information about the project's performance [7,24]. Managers should not only recognize opportunities using these options but also manage projects to maximize its expected value.…”
Section: Option Based Evaluationmentioning
confidence: 99%
“…As mentioned above, current studies that measured the value of risky projects and used NPV or ROA stopped at the initial decision and neglected to investigate the impact of the way the project is managed on its business value. A project includes one or more real option opportunities when managers have the option, but not the obligation to adjust the future direction of the project in response to information about the project's performance [7,24]. Managers should not only recognize opportunities using these options but also manage projects to maximize its expected value.…”
Section: Option Based Evaluationmentioning
confidence: 99%
“…For example, real options perspective is used to evaluate the costs and benefits of different approaches, and select future IT investments (Chulkov andDesai 2008, Tiwana et al 2006). Under high velocity or equivocal situations, information gathered may have multiple interpretations -e.g., positive or negative, biased or unbiased (Bowen 1987).…”
Section: Velocity and Uncertainty In Organizational Processes And Effmentioning
confidence: 99%
“…Several studies pointed the causes to the drawbacks of traditional capital budgeting techniques (Chulkov and Desai 2008;Keil and Flatto 1999;Taudes et al 2000;Tiwana et al 2006;Tiwana et al 2007). Keil and Robey (1999) indicated that escalations may be the result of equivocal situations formed by a lack of clarity about projects' success and failure criteria.…”
Section: Related Research: Is/it Projects Evaluation and Continuationmentioning
confidence: 99%
“…Unraveling Equivocality in Evaluations of Information Systems Projects (Chulkov and Desai 2008). In certain cases, escalating a project is needed and considered to be rational based on this view (Tiwana et al 2006).…”
Section: Related Researchmentioning
confidence: 99%
See 1 more Smart Citation